2007
DOI: 10.1007/s10499-007-9072-7
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perception versus scientific evidence of farmed and wild fish: exploratory insights from Belgium

Wim Verbeke,
Isabelle Sioen,
Karen Brunsø
et al.

Abstract: The increasing number of marketable fish being supplied from aquaculture is a response to the increasing demand for healthy food and is filling the gap left by depleting natural fish stocks. Little is known about the awareness and perception of the consumer in terms of farmed fish versus fish from capture fisheries. The consumer's subjective point of view is of overriding importance for the production system and product acceptance as well as for future market success. In this paper consumer perception in Belgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
112
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 23 publications
13
112
0
1
Order By: Relevance
“…The limited level of knowledge about seafood production systems and environmental impacts from capture fisheries and aquaculture found in this study agrees with results from earlier work, e.g., [12,63,64]. The extent of label recognition differed substantially between logos presented, ranging from 95% for the organic label KRAV to only 23% for ASC.…”
Section: Discussionsupporting
confidence: 86%
“…The limited level of knowledge about seafood production systems and environmental impacts from capture fisheries and aquaculture found in this study agrees with results from earlier work, e.g., [12,63,64]. The extent of label recognition differed substantially between logos presented, ranging from 95% for the organic label KRAV to only 23% for ASC.…”
Section: Discussionsupporting
confidence: 86%
“…This result is surprising because the lack of knowledge was frequently purported to be a reason for the lack of interest and preference for sustainable fish (Feucht & Zander, 2015) because consumers might underestimate the consequences of their purchase decisions for or against sustainable products due to their lack of knowledge (Brécard, Hlaimi, Lucas, Perraudeau, & Salladarre, 2009). Different studies highlight the fact that knowledge about seafood seems to be frequently limited even though a generic understanding of sustainability in seafood exists Arvanitoyannis, Krystallis, Panagiotaki, & Theodorou, 2004;Feucht & Zander, 2015;Gutierrez & Thornton, 2014;Schlag & Ystgaard, 2013;Verbeke et al, 2007a). Almeida, Altintzoglou, Cabral, & Vaz (2015) and Honkanen, Olsen, & Verplanken (2005) highlighted that higher knowledge is not necessarily related to more sustainable seafood choices.…”
Section: Wtp In Different Consumer Segmentsmentioning
confidence: 99%
“…It has been recently demonstrated that fish origin (wild or farmed) and rearing techniques both affect consumer perceptions of fillet quality. According to Verbeke et al (2007), a large majority of consumers believes there are no major differences between farmed and wild fish, even if taste perception is mostly in favour of wild fish. With respect to aquacultured products, the type of farming could be relevant in consumer choices.…”
Section: Introductionmentioning
confidence: 99%